Heterophase ﬂuctuations in glass-forming liquids and random ﬁeld Ising model - Bakai, A.S. (Condensed Matter Physics, 2000)
The liquid-to-glass transition is a process of supercooled liquid solidiﬁcation. Rather large density ﬂuctuations are revealed experimentally in many
of the glass-forming liquids above the glass transition temperature while
no phase transitions are identiﬁed [1,2]. In [3–5], the inhomogeneities are
treated as heterophase ﬂuctuations (HPF). The process of glass formation gets there a natural description as a continuous phase transformation.
The theory of strong HPF was developed in a mean ﬁeld approximation
which ignores the mesoscopic structure of the inhomogeneities which is
an issue of extensive experimental investigations and discussions [1,2,5].
In the present communication the HPF are considered in the model of interpercolating heterophase states and in Ginzburg-Landau (GL) approach.
It is shown that the GL approach results in the random ﬁeld Ising model
(RFIM) for HPF. It permits to get a description of the medium range and
long-range correlations of the HPF. RFIM is very useful in studying the spin
systems with a frozen-in disorder. Therefore the theory developed makes
it possible to compare the phase states with frozen-in (spin systems) and
self-consistent (heterophase liquids) disorders. In particular, it turns out
that the heterophase liquids are similar (but not identical) to Grifﬁths phase
of disordered spin systems. It is seen that the developed model bridges the
theories of disordered spin systems and glass-forming liquids. Утворення скла є процесом твердiння переохолодженої рідини. Експериментально виявлено досить великі флуктуації густини в багатьох
склоутворюючих рідинах вище температури вітрифікації, але, разом
з тим, жодних ознак фазового переходу не спостерігається [1,2].
В [3–5] ці неоднорідності розглядаються як гетерофазні флуктуації
(ГФФ), процес утворення скла описується як неперервне фазове перетворення. Теорію сильних ГФФ тут розвинуто в наближенні середнього поля, в якому ігнорується мезоскопічна структура неоднорорідностей, які є предметом інтенсивних експериментальних досліджень та обговорювань [1,2,5]. В цьому повідомленні ГФФ розглянуто в межах моделі інтерперкольованих кластерів та в підході
Гінзбурга-Ландау (ГЛ). Показано, що наближення ГЛ приводить до
моделі Ізінга у випадковому полі (МІВП). Це дозволяє розглядати кореляції ГФФ на проміжних та довгих масштабах. МІВП широко використовується при розгляді спінових систем з вмороженим безладом. Через це розроблена теорія дає можливість порівнювати фазові
стани систем з вмороженим (спінові системи) та самоузгодженим
(гетерофазні рідини) безладами. Зокрема виявляється, що гетерофазні рідини є подібні (але не ідентичні) до фази Гріфіца невпорядкованої спінової системи. Як бачимо, розроблена модель встановлює
зв’язок між теоріями спінових систем та склоутворюючих рідин.